Stroke Risk Factors in Public Sector Hospitals, Peshawar - Musa, Nighat; Khan, Asghar; Ayub, Sher (Journal of Gandhara Medical and Dental Science, 2020)
OBJECTIVES: To determine the incidence of risk factors regarding stroke amid diagnosed patients in public sector hospitals of Peshawar. METHODOLOGY: The study design was cross sectional. Duration of the study was from May till August 2018. It was conducted in two public sector hospitals of Peshawar (Khyber Teaching Hospital and Lady Reading Hospital). A total of 300 patients participated after taking informed consent. Convenient sampling technique was used. Data was entered in excel sheets and then imported for analysis in SPSS version 21. RESULTS: Study results showed that 62% patients were males and 38% were females. Males age distribution less than 40 years were 24% and more than 41 years were 76%. Similarly, females were 21% and 79% respectively. Major medical risk factors found were hypertension, diabetes and cardiovascular diseases. The environmental risk factors were physical inactivity, smoking and obesity. The less common risk factors were alcohol and oral contraceptive use. CONCLUSION: The identified medical risk factors in the study can be improved and modified by regular check-ups and drug compliance. However, the environmental factors including physical inactivity, smoking and obesity can be reversed by acquiring healthy lifestyles. KEYWORDS: Stroke, Hypertension, Obese, Diabetes, Smoking